Molecular reaction dynamics - Levine, Raphael D. (Cambridge University Press, 2005)
Molecular Reaction Dynamics is a brand new version of the classic text by Levine and Bernstein. The book describes fundamental theory, experimental techniques and developing research. With problems sets included, this book will be suitable for those studying chemical reaction dynamics, and will supplement physical chemistry and natural science courses.